Design and Construction of Computer Numeric Control (CNC) Machines Based on Microcontrollers - Iqbal rasikin; Hamdani; Pristisal Wibowo (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Computer Numerical Control (CNC) is a technology that allows automatic control of machine tools through programmed commands. This research aims to design and build microcontroller-based CNC machines for material cutting applications. The use of microcontrollers as the main control is expected to provide flexibility and efficiency in CNC machine operations.The research methodology includes the stages of conceptual design, component selection, electronic system manufacturing, operational testing, and engine performance evaluation. The designed CNC machine uses a microcontroller controller to drive the stepper motor and control the cutting process based on G-Code data. The results show that this microcontroller-based CNC machine is able to produce cuts with an adequate level of accuracy and precision for material processing applications. Performance evaluations show that the machine can operate a wide range of sizes and types of cuts with consistent results. The implementation of microcontroller-based CNC machines can be an effective alternative in the development of material processing technology with reliable and adaptive automatic control to various industrial applications.